Innovations in state and municipal management as a necessary condition for the social and economic development of the state - Nadezhda Evgenievna Prodiblokh; Marietta Askarbievna Bolokova (Вестник Майкопского государственного технологического университета)
There is no doubt that at present the traditional roles of government and public administration must adapt to the emerging and future needs of the society. In this context, it should be noted that innovative technologies can bring new possibilities to the public sector, improve the interaction between government and citizens by simplifying procedures, and promote government openness. Redesigning political institutions and rethinking government can make political institutions more interactive and effective. All considered, the aim of the article is to study distinctive features of the introduction and implementation of innovation in the system of state and municipal government in Russia to ensure the socio-economic development of the country. The research methods include general theoretical and special methods of knowledge, namely analysis, synthesis, comparison, generalization, systematization, prediction, extrapolation. In the process of the research special attention is paid to the influence of innovations on the social and economic development of the country at the state level, which is determined by the example of three main levels of their implementation, covering almost all spheres of social life. At the local level, the advantages of using innovations in the activities of public authorities have been analyzed in the context of citizens, business structures and non-profit organizations, as well as the local authorities themselves. According to the results of the research, proposals have been formulated concerning the development of scientific and methodological support of innovative activities of public authorities inRussia and intensifying the use of progressive financial instruments that contribute to the emergence of managerial innovations.